2012
DOI: 10.1177/2158244012455179
|View full text |Cite
|
Sign up to set email alerts
|

“The Missing Link”

Abstract: Critical examinations of epistemology argue that White men have established the guidelines for scientific knowledge. Because other groups were never allotted the opportunity to contribute to the immense knowledge base, the Western scientific knowledge base remains deficient. The author calls for a more inclusive knowledge base that includes the voices of Black women in the field of psychology. This inclusion is critical to better equip mental health clinicians to handle the unique needs of this population. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Black, Latina, and other women of color, who are further marginalized by the interaction of gender and race, are particularly absent in neuroscience research ( Spates, 2012 ; Gatzke-Kopp, 2016 ). For example, a systematic literature review reported that women and racial/ethnic minorities were underrepresented in functional magnetic resonance imaging (fMRI) studies of cardiovascular disease ( Jones et al, 2020 ).…”
Section: Bias In Neuroscientific Researchmentioning
confidence: 99%
“…Black, Latina, and other women of color, who are further marginalized by the interaction of gender and race, are particularly absent in neuroscience research ( Spates, 2012 ; Gatzke-Kopp, 2016 ). For example, a systematic literature review reported that women and racial/ethnic minorities were underrepresented in functional magnetic resonance imaging (fMRI) studies of cardiovascular disease ( Jones et al, 2020 ).…”
Section: Bias In Neuroscientific Researchmentioning
confidence: 99%
“…Therefore, open science as a field should respond to these concerns by working to distribute power more equally and democratize knowledge-making (Istratii & Porter, 2018;Spates, 2012). Open science advocates should re-examine past practices to demonstrate awareness of cultural biases which reinforce unequal power structures in open science, so as not to perpetuate Eurocentric discourse and enforce the social values that (re)create power imbalances (Spates, 2012). In this context, before encouraging openness as a status quo in psychological science, we must consider what else is being opened up in the process and who governs this process (Bahlai et al, 2019).…”
Section: Barriers To Participation In Open Science As a Feminist Ecrmentioning
confidence: 99%
“…To begin, in the western sciences, Black women's psychology has routinely been relegated to the margins (Spates, 2012;Cole, 2020), and therefore much is still left to be researched, and understood, about Black women's lived experiences, beyond the field of sociology (Collins, 2009). As a direct consequence of this gap, the process of surveying literature on the psychology of Black women (Spates, 2012;Thomas, 2004;Cole, 2020), within the context of this research, was found to be a predictably challenging endeavour. Not only, was this compounded by the dearth of research available, on Black women, more generally, in psychology, but also within this…”
Section: Synthesising Literature Across Academic Disciplinesmentioning
confidence: 96%
“…(Mirza, 1997), who indicated the importance of "placing the remembered past" at the centre of her own analysis (1997, p. 191), which I intend to do here. Also, to address the research aims, and probable causes for underresearched lived experiences, which continue to persist in the study of the psychology of Black women (Cole, 2020;Spates, 2012;Thomas, 2004) and the Western sciences, more generally, this section also sought to integrate literature, institutional, and governmental publications that could highlight the fundamental role the Western sciences played in the development of "arbitrary constructions of human division" (Wilkerson, 2020, p. 37), rooted in White supremacist ideology, as it could be said to operationalise in the WEIRD music industry. As this harmful belief and indoctrination system still massively impacts Black people, people of colour (POC), as well as White minority and ethnic groups, in both societies today (Yakushko, 2019), this was important to centre, to frame how this informed this research.…”
Section: Constructionsmentioning
confidence: 99%
See 1 more Smart Citation